PREVALENCE OF FURCATION INVOLVEMENT IN PATIENTS WITH CHRONIC PERIODONTITIS VISITING DENTAL COLLEGE- RETROSPECTIVE STUDY - Karpagam, G.Nithya; Malaiappan, Sankari; Prabu, Dinesh (International Journal of Psychosocial Rehabilitation, 2025)
The aim of the study is to assess the furcation involvement among chronic periodontitis patients visiting dental college. It was a retrospective study of patients reported to Saveetha Dental College And Hospitals, with periodontitis. Data was obtained by evaluating 86000 patients records. Out of which 72 patients with chronic periodontitis were evaluated in this study. Data extraction was done and was segregated based on demographic data age and gender. The periodontal parameters namely clinical attachment loss, probing depth and furcation involvement based on Glickman's classification were recorded. The data were collected and entered in the excel sheet. After data collection descriptive and inferential statistical analysis was done in IBM SPSS software version 20. This study shows that the most prevalent age group with furcation involvement in chronic periodontitis was 46-55 years. Males were more commonly affected than females. Prevalence of furcation involvement was found to be more in maxillary molar than in the mandibular molar. The most prevalent grade of furcation involved in the maxillary first molar is grade II. The association between the grade of furcation with age and gender was found to be statistically significant.